Numerical modeling of intrachamber processes at the output settlement mode of a solid propellant rocket engine - Amarantov, Georgy Nikolaevich; Egorov, Mikhail Yur'evich; Egorov, Sergey Mikhailovich; Egorov, Dmitry Mikhailovich; Nekrasov, Valentin Ivanovich (Computational Continuum Mechanics, 2010)
Complex numerical modeling of the intrachamber processes, proceeding at the output settlement mode of operation of a solid propellant rocket engine, is carried out. We consider the coupled problem, which involves non-stationary operation of an ignition device; warming up, ignition and subsequent non-stationary burning of a propellant grain; non-stationary three-phase homogeneous-heterogeneous flow of the products of combustion in the combustion chamber, in the nozzle and behind the nozzle of the rocket engine; depressurization and moving of the nozzle block membrane. The results of modeling are given.
Keywords: numerical modeling; inside chamber processes; solid propellant rocket engine